Rancang Bangun Sistem Kontrol Tekanan Hydrophore Tank Berbasis IoT - Andy Dwi Ardiyanto; Antonius Edy Kristiyono; Akhmad Kasan Gupron (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Fresh water is one of the essential needs in ship operations, used for daily needs such as cooking, bathing, and washing, as well as supporting the function of equipment in the engine room. Fresh water distribution on ships is generally carried out using hydrophore tanks, which are pressurized tanks that utilize compressed air to distribute water throughout the system. However, in practice, hydrophore tanks often face problems in the pressure system due to reduced air volume, which can disrupt the smooth distribution of fresh water and reduce the ship's work efficiency. To address these problems, this study uses the Research and Development (R&D) method by designing an Internet of Things (loT)-based control and monitoring system. The system is designed through the integration of pressure sensors, water level sensors, ESP32 microcontrollers, solenoid valves, and buzzers. Testing is carried out in stages through static tests, dynamic tests, and actual integrated testing to ensure system reliability. The test results show that the system is able to monitor air pressure and water level in real-time, as well as control solenoid valves and pumps automatically when the pressure is below the minimum limit or exceeds the maximum threshold. Sensor data was successfully transmitted via WiFi to a web server and Android app, allowing ship operators to perform remote monitoring and receive notifications when overpressure or underpressure occurs. Thus, this loT-based hydrophore pressure control system has proven effective in maintaining pressure stability and improving the efficiency of freshwater distribution on board ships. This system also has the potential to be further developed by adding a cloud-based data storage feature for more comprehensive long-term pressure trend analysis.